2009
DOI: 10.1007/s00535-009-0066-2
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of correlation between serum pepsinogen concentrations and gastric acid secretion after H. pylori eradication

Abstract: Using different serum biomarkers (pepsinogen I/II ratio prior to eradication or pepsinogen I after eradication), the measurement of serum pepsinogens is useful for predicting the individual gastric acid secretion level not only in H. pylori-infected subjects, but also in subjects with histories of eradication of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…pylori eradication. After H. pylori eradication, PGI acted as a superior predictor for gastric mucosal secretion than the PGI/PGII ratio[24], partly due to the increase in PGI/PGII ratio after H. pylori eradication [25] which is mirrored the PGII reduction after relatively healing of inflammation. This finding suggests that PGI and PGII are markers for two different stages of fundic atrophy development.…”
Section: Discussionmentioning
confidence: 98%
“…pylori eradication. After H. pylori eradication, PGI acted as a superior predictor for gastric mucosal secretion than the PGI/PGII ratio[24], partly due to the increase in PGI/PGII ratio after H. pylori eradication [25] which is mirrored the PGII reduction after relatively healing of inflammation. This finding suggests that PGI and PGII are markers for two different stages of fundic atrophy development.…”
Section: Discussionmentioning
confidence: 98%
“…However, IgG antibody test showed high sensitivity and specificity over 90% for diagnosing H. pylori infection (Wilcox et al 1996;Sasazuki et al 2006) and it would be practical in clinical settings to measure both H. pylori antibody and pepsinogen concentrations using the same serum samples. Finally, the PG cutoff values calculated in the present analysis could not be applied to those with a history of H. pylori eradication because the correlation between gastric acid secretion and serum PGs is considerably altered after the therapy (Iijima et al 2009b). Since we have recently reported that gastric acid secretory capacity is inversely associated with the risk for gastric carcinoma emerging after successful eradication (Iijima et al 2012), the serum PG values after eradication might be useful for estimation of the cancer risk among eradicated patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, PGI level generally does not increase after eradication [17,18,34]. Second, low PGI level is associated with increased acid secretion after eradication, suggesting that PGI level would decrease synchronously with recovery from atrophy [35]. …”
Section: Discussionmentioning
confidence: 99%